Agricultural and Aquaculture Wastes as Concrete Components: A Review - Wei Wang (Frontiers Media S.A., 2021)
The application of agricultural and aquaculture waste in concrete greatly reduces the pressure on the ecological environment brought by traditional concrete production. The use of agricultural and aquaculture wastes as cement replacement, aggregate replacement and fiber reinforcement has showed great potential. Making full use of these wastes can help the development of sustainable concrete. This paper provides an objective evaluation and summary of agricultural waste and aquaculture waste in green concrete. Agricultural waste is divided into natural plant fiber, agricultural waste ash and multi-application waste according to useful function and alternative methods, such as sisal fiber, olive waste ash, and bamboo. Aquaculture waste mainly refers to some shells such as oyster shell. This paper analyzes the advantages and disadvantages of agricultural and aquaculture waste concrete applications that have been reported and shows how different agricultural and aquaculture wastes are made in concrete. The selection of appropriate treatment methods and usage scenarios is extremely important for agricultural and aquaculture waste concrete, which can determine whether the concrete has reliable performance. This paper will lay a foundation for the progress of waste concrete and provide reliable help for the development of environmental protection concrete.